Review on Wind Turbine Technology and Control - M. Murad, N. S. F.; Kamarudin, M. N.; M. Rozali, S.; M. Shaharudin, N. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
This paper provided a review on wind turbine technology and control. The technologies, differences, advantages and disadvantages of horizontal and vertical axis wind turbine structures were reported. The control strategies of wind turbine such as fixed speed and variable speed were also discussed along with the wind turbine distribution profile for both vertical and horizontal axis configuration. The aim is to cover the appropriate wind turbine structures and control strategies to be used in the certain area condition. Regardless similar wind speed distribution profile except the power coefficient, horizontal axis wind turbine (HAWT) and vertical axis wind turbine (VAWT) have different structures and control strategies. As a conclusion, HAWT structure is less suitable for urban area as compared to VAWT nevertheless is more appropriate for large-scale wind farm. For the control approach, variable speed wind turbine (VSWT) is more appropriate for high wind speed area due to its ability to achieve maximum efficiency as compared to a fixed speed wind turbine (VSWT).